Negotiating disability in everyday life: ethnographical accounts of women with rheumatoid arthritis. (March 2014) - Prodinger, Birgit; Shaw, Lynn; Laliberte Rudman, Debbie; Stamm, Tanja
Abstract Purpose: Drawing on data from a larger study, the aim of this paper is to illuminate how the everyday doings of women with disabilities are coordinated to and shaped by organizational processes and social context, particularly as these relate to the potential of being labelled disabled. Methods: An institutional ethnography was conducted with seven Austrian women diagnosed with rheumatoid arthritis (RA). Interviews and participant observations were conducted, and texts about the historical development of disability policies were identified. Data analysis included grouping similar doings of participants together to subsequently explore links between what the women did and how their doings are shaped by disability policies and the social context. Results: The women, who participated in this study, spent time and effort to keep the disease invisible, resist disability and negotiate a disability pass. By drawing upon the historical development of Austrian disability policies, the interpretation reveals how this development infiltrates into participants' lives and shapes their everyday doing. Conclusion: This study furthers understanding of how broader policies and practices, shaped over historical time, infiltrate into the daily lives of women with disabilities. It illustrates how full participation may not necessarily be a lived reality for people with disabilities at this point in Austria. Implications for Rehabilitation Maximising full participation for people with rheumatoid arthritis is important. This requires focusing not only on the bodily health of people with rheumatoid arthritis but also on their interaction with the social, cultural and political context in their daily lives. This requires also understanding how knowledge about disability is passed on from previous generations.